Multi-element interface-stable high-voltage all-solid-state battery positive electrode material, preparation method and electrochemical device
By forming a multi-element high-entropy oxide interface layer on the positive electrode material of all solid state battery, the volume change and irreversible phase change of traditional positive electrode materials during high-voltage cycle are solved, and the cycle performance and stability of the battery are significantly improved.
Patent Information
- Application Number
- CN202411297582.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-18
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2044-09-18
AI Technical Summary
Traditional all-solid-state battery positive electrode materials have volume changes and irreversible phase change during high-voltage cycles, resulting in poor interface contact and poor performance. The existing surface coating and single element doping are difficult to effectively solve.
Using multi-element high-entropy oxide interface layer, a perovskite-like doped layer is formed by doping elements such as La, Ca, Mg, Lu, Eu, etc., as the surface layer of the positive electrode material, to alleviate interface reactions and volume changes, and improve the Interface stability.
It significantly improves the circulation performance and stability of the positive electrode material, extends the battery life, and improves the energy density and rate performance of all-solid-state batteries.
Smart Images

Figure CN119153654A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of battery materials, and in particular to a multi-element interface-stable high-voltage all-solid-state battery positive electrode material, a preparation method and an electrochemical device. Background Art
[0002] In recent years, based on energy demand and environmental protection requirements, the design and manufacture of chemical power sources with high energy storage capacity and high safety has become one of the research topics that has attracted much attention in the new century. Lithium-ion batteries play an important role in consumer electronics, electric vehicles, aerospace and other fields due to their excellent performance. However, traditional liquid lithium-ion batteries have many defects in terms of energy density, safety and environmental friendliness.
[0003] In contrast, all-solid-state batteries based on metallic lithium negative electrodes have attracted much attention due to their high safety and high energy density, and have become a current research hotspot. However, all-solid-state batteries still face some key problems in practical applications, such as serious interface reactions and poor interface contact between the positive electrode material and the solid electrolyte, which affect the performance of all-solid-state batteries. Researchers suppress interfacial side reactions and mechanical stability by surface coating and element doping of the positive electrode. However, traditional surface coatings and single element doping are difficult to match the volume changes and irreversible phase changes of the positive electrode material during high-voltage cycling, and have limited inhibitory effects on the escape of positive electrode lattice oxygen.
[0004] It should be noted that the information disclosed in the above background technology section is only used for understanding the background of the present application, and therefore may include information that does not constitute prior art known to ordinary technicians in the field. Summary of the invention
[0005] The main purpose of the present invention is to solve at least one of the above technical problems and provide a multi-element interface stable high-voltage all-solid-state battery positive electrode material, a preparation method and an electrochemical device.
[0006] To achieve the above object, the present invention adopts the following technical solutions:
[0007] In the first aspect of the present invention, a multi-element interface-stabilized high-voltage all-solid-state battery positive electrode material is provided, the positive electrode material comprising a core and a doping layer located on the surface of the core, wherein the core is a lithium-containing layered oxide, and the doping layer is a multi-element high-entropy oxide interface layer of a perovskite-like phase.
[0008] In some optional embodiments, the doping layer contains doping elements, and the doping elements include at least five of La, Ca, Mg, Lu, Eu, Al, Mo, Ta, Ti, V, Cr, Fe, Cu, Zn, Zr and Nb.
[0009] In some optional embodiments, the doping elements are composed of La, Ca, Mg, Lu and Eu; the molar amount of each element in the doping elements is 5% to 20% of the molar amount of lithium element in the core.
[0010] In some optional embodiments, the thickness of the doping layer is 20 nm to 30 nm.
[0011] In a second aspect of the present invention, a method for preparing a multi-element interface-stable high-voltage all-solid-state battery positive electrode material comprises the following steps:
[0012] dissolving a doping metal source in water or an organic reagent to obtain a precursor solution, wherein the doping metal source includes a doping element;
[0013] Adding lithium-containing positive electrode particles to the precursor solution and mixing to generate solid particles, which are then dried to obtain a powder material; and
[0014] The powder material is sintered to obtain the multi-element interface-stable high-voltage all-solid-state battery positive electrode material, wherein in the multi-element interface-stable high-voltage all-solid-state battery positive electrode material, the doping element is located on the surface of the lithium-containing positive electrode particles to form a doping layer, and the doping layer is a multi-element high-entropy oxide interface layer of a perovskite-like phase.
[0015] In some optional embodiments, the doping elements include at least five of La, Ca, Mg, Lu, Eu, Al, Mo, Ta, Ti, V, Cr, Fe, Cu, Zn, Zr and Nb.
[0016] In some optional embodiments, the doping element consists of La, Ca, Mg, Lu and Eu;
[0017] The molar amount of each element in the doping element is 5% to 20% of the molar amount of the lithium element in the core.
[0018] In some optional embodiments, in the step of adding the lithium-containing positive electrode particles to the precursor solution for mixing, the mixing temperature is 25° C. to 100° C., and the mixing time is 6 h to 24 h.
[0019] In some optional embodiments, the sintering heating rate is 1°C / min to 5°C / min, the sintering temperature is 400°C to 800°C, the sintering time is 4h to 8h, and the sintering atmosphere is an oxygen atmosphere.
[0020] In the third aspect of the present invention, an electrochemical device comprises a positive electrode plate, a negative electrode plate and a solid electrolyte, wherein the positive electrode plate comprises a positive electrode material, and the positive electrode material is a multi-element interface-stabilized high-voltage all-solid-state battery positive electrode material as described above.
[0021] The present invention has the following beneficial effects:
[0022] The present invention provides a multi-element interface-stable high-voltage all-solid-state battery positive electrode material and a preparation method and application thereof, wherein the positive electrode material comprises a core and a doping layer located on the surface of the core, wherein the core is a lithium-containing layered oxide, and the doping layer is a multi-element high-entropy oxide interface layer. The positive electrode material has a perovskite-like high-entropy oxide interface layer, which effectively alleviates the interface side reaction between the positive electrode material and the solid electrolyte, inhibits the volume change of the positive electrode material during the charge and discharge process, reduces the risk of poor contact of the solid-solid interface on the positive electrode side, improves the cycle performance of the positive electrode material, and thus improves the stability of the positive electrode interface. At the same time, the interface layer alleviates the irreversible phase change and lattice oxygen loss of the positive electrode material during the high-voltage cycle process, improves the upper limit cutoff voltage of the positive electrode material, and realizes a high specific energy and long cycle life all-solid-state battery.
[0023] Compared with the prior art, the multi-element interface-stable high-voltage all-solid-state battery positive electrode material provided by the present invention has a doped layer, which is a multi-element high-entropy oxide interface layer of a perovskite-like phase, with high electronic conductivity and low oxygen ion conductivity, which can act as an oxygen ion buffer layer of the core, relieving the escape of lattice oxygen on the surface of the positive electrode material during charging and discharging, and helping to enhance the interface stability between the positive electrode material and the solid electrolyte. By increasing the entropy value of the interface layer, the interface side reaction between the positive electrode material and the solid electrolyte is effectively alleviated, while suppressing the volume change of the positive electrode material during charging and discharging, reducing the risk of poor contact of the solid-solid interface on the positive electrode side, and improving the cycle performance of the positive electrode material, thereby improving the stability of the positive electrode interface of the electrochemical device (such as an all-solid-state battery).
[0024] Other beneficial effects of the embodiments of the present invention will be further described below. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 A process flow chart of a method for preparing a multi-element interface-stable high-voltage all-solid-state battery positive electrode material provided in an embodiment of the present application.
[0026] Figure 2 1 and 2 are XRD diagrams of the positive electrode materials prepared in Example 1, Example 2 and Comparative Example 1 of the present application.
[0027] Figure 3AThis is a comparison chart of the long cycle performance of all-solid-state batteries based on Li3InCl6 solid electrolyte at 0.5C of the positive electrode materials prepared in Example 1, Example 2 and Comparative Example 1 of the present application.
[0028] Figure 3B This is a comparison chart of the long cycle performance of the all-solid-state battery based on Li3InCl6 solid electrolyte at 0.5C for the positive electrode materials prepared in Example 3 of the present application and Comparative Example 2.
[0029] Figure 4A This is a comparison chart of the rate performance of all-solid-state batteries based on Li3InCl6 solid electrolyte with positive electrode materials prepared in Example 1, Example 2, Comparative Example 1 and Comparative Example 3 of the present application.
[0030] Figure 4B This is a comparison chart of the rate performance of all-solid-state batteries based on Li3InCl6 solid electrolyte with positive electrode materials prepared in Example 3 and Comparative Example 2 of the present application.
[0031] Figure 5 This is a comparison chart of the high voltage cycling performance of an all-solid-state battery based on Li3InCl6 solid electrolyte and the positive electrode material prepared in Example 1 of the present application and Comparative Example 1. DETAILED DESCRIPTION
[0032] The following is a detailed description of the embodiments of the present invention. It should be emphasized that the following description is only exemplary and is not intended to limit the scope and application of the present invention.
[0033] It should be noted that the present invention is based on the following findings of the inventors: The inventors have found that the single element bulk doping in the positive electrode material has limited inhibitory effect on the interface side reaction and will cause loss of the capacity of the positive electrode material; the positive electrode surface coating method is difficult to achieve completely uniform thin layer coating, and the coating layer is difficult to adapt to the volume change of the positive electrode material during the cycle. Even by single bulk doping or surface coating of the positive electrode material, there are still problems such as poor solid-solid interface contact, serious side reactions, volume change of the positive electrode material during the cycle, and poor stability under high voltage.
[0034] An embodiment of the present application provides a multi-element interface-stabilized high-voltage all-solid-state battery positive electrode material, the positive electrode material comprising a core and a doping layer located on the surface of the core, wherein the core is a lithium-containing layered oxide, and the doping layer is a multi-element high-entropy oxide interface layer of a perovskite-like phase.
[0035] In some embodiments, the lithium-containing layered oxide core can be lithium cobalt oxide and / or nickel-cobalt-manganese ternary positive electrode materials. The above materials are selected as the positive electrode material core for use in all-solid-state lithium-ion batteries. Due to their stable structure and good electrical conductivity, they can ensure the energy density and safety of all-solid-state lithium-ion batteries. However, there are serious interface reactions, poor contact, and space charge layers between the above positive electrode materials and solid electrolytes.
[0036] To this end, the embodiment of the present application performs multi-element surface high entropy doping on lithium-containing layered oxides to form a doped layer. The atomic arrangement in the doped layer is random and disordered, resulting in an increase in the configuration entropy of the doped layer and causing lattice distortion. These microstructural features enable the positive electrode material to exhibit excellent performance, such as chemical stability, good cycle performance, rate performance, and high-voltage stability performance. The doped layer is a perovskite-like phase. This multi-component, structurally stable perovskite-like phase interface layer has high lithium ion conductivity, high electronic conductivity, and low oxygen ion conductivity. It can act as an oxygen ion buffer layer, which alleviates the escape of lattice oxygen on the surface of the positive electrode during charging and discharging, hinders the diffusion of decomposition byproducts of the solid electrolyte, and helps to enhance the interface stability between the positive electrode material and the solid electrolyte. In an all-solid-state battery, the interface between the positive electrode material and the solid electrolyte is crucial to the battery performance. A stable interface can reduce the polarization and resistance of the battery during charging and discharging, which is beneficial to improving the cycle performance and long-term stability of the battery. There are also a large number of oxygen vacancies in the interface layer, which can prevent the loss of lattice oxygen in the positive electrode material during charging and discharging. At the same time, the interface layer has higher ionic conductivity and electronic conductivity than the layered structure of the inner core, which helps to promote the rapid transport of ions and electrons on the positive electrode side, thereby improving the rate performance of the prepared battery.
[0037] Specifically, the doping elements contained in the doping layer may include at least five of La, Ca, Mg, Lu, Eu, Al, Mo, Ta, Ti, V, Cr, Fe, Cu, Zn, Zr and Nb, etc. The high entropy oxide doping layers formed by different doping elements have certain differences in electrochemical properties, and the above doping elements can be selected according to actual needs.
[0038] Among them, La, Lu, Eu, Mo, Ta, Ti, V, Cr, Fe, Cu, Zn, Zr and Nb belong to transition metal elements. The doping of the above transition metal elements can change the electronic structure and charge transfer characteristics of the layered oxide positive electrode materials, thereby improving their electrochemical performance, such as improving the discharge capacity and cycle stability; it can also stabilize the layered structure, inhibit the structural evolution of the material during the cycle and the capacity decay of the electrode material, and extend the life of the battery; at the same time, it can fine-tune the lattice parameters and crystal structure of the positive electrode material, and improve the distribution of the electrochemical active sites and electrochemical performance of the positive electrode material. Moreover, La, Lu and Eu are all lanthanide elements with similar chemical properties, which are conducive to enhancing the crystal structure stability of the positive electrode material and reducing the structural defects caused by doping.
[0039] Ca, Mg and Al are non-transition metals. + The ionic radius of the positive electrode) or the bond energy of the bond formed with oxygen is large, which can stabilize the crystal structure framework during the lithium ion extraction / embedding process, enhance the mechanical stability and structural strength of the positive electrode material, and reduce its microcracks and particle peeling during the cycle; it can also regulate the electronic structure of the positive electrode material and improve the delithiation potential of the positive electrode material. The doping of elements such as Ca, Mg and Al helps to enhance the electronic conductivity of the positive electrode material and promote the rapid transmission of electrons, thereby improving the energy density and charge and discharge rate of the battery. At the same time, Ca and Mg are also elements of the same group and have similar chemical properties, which is conducive to enhancing the crystal structure stability of the positive electrode material and reducing structural defects caused by doping.
[0040] Furthermore, the doping elements can be composed of La, Ca, Mg, Lu and Eu. The above five elements are used for doping. Since La, Lu and Eu are all lanthanide elements, and Ca and Mg are also alkaline earth metal elements, they all have similar chemical properties and jointly complete the construction of the interface structure of the high entropy oxide layer of the perovskite phase, which is beneficial to enhance the crystal structure stability of the positive electrode material.
[0041] In some embodiments, the thickness of the doping layer may be 20 nm to 30 nm, further 20 nm to 25 nm, illustratively 20 nm, 21 nm, 22 nm, 23 nm, 24 nm, 25 nm, 26 nm, 27 nm, 28 nm, 29 nm or 30 nm, etc. Within the above range, the doping layer can effectively stabilize the reaction interface between the positive electrode material and the solid electrolyte.
[0042] In some embodiments, the molar amount of each element in the doping element in the doping layer can be 5% to 20% of the molar amount of the lithium element in the doping layer, for example, it can be 5% to 7% or 12% to 15%, and can be 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19% or 20%, etc. Controlling the molar amount of each doping element in the doping layer to be 5% to 20% of the molar amount of the lithium element can reduce the volume expansion of the battery during the charge and discharge process and the side effects of the chemical reaction, thereby improving the safety of the battery and extending its service life.
[0043] Furthermore, the molar amounts of each element in the doping element in the doping layer can be similar, and further, the molar amounts of each element in the doping element can be the same. Controlling the molar amounts of each element to be similar or the same can maximize the entropy effect in the material, ensure the random distribution and arrangement of multiple elements in the doping elements, and increase the irregularity of the structure and properties of the doping layer. This irregularity can increase the thermal stability and electrochemical stability of the positive electrode material, and improve the energy density and power density. The doping design with the same molar amount of each element helps to maintain the balance and stability of the material structure, avoid uneven reactions caused by local excess elements, and thus improve the long-term stability and reliability of the battery.
[0044] Compared with the prior art, the multi-element interface-stable high-voltage all-solid-state battery positive electrode material provided in the embodiments of the present application has the following beneficial effects:
[0045] 1. The positive electrode material has a multi-element high entropy oxide interface layer as a doping layer, which effectively alleviates the interface side reaction between the positive electrode material and the solid electrolyte, and at the same time inhibits the serious volume change and irreversible phase change of the positive electrode material during high-voltage cycling, reduces the risk of poor contact of the solid-solid interface on the positive electrode side, and improves the high-voltage cycling performance of the positive electrode material, thereby enhancing the stability of the positive electrode interface of the electrochemical device (such as an all-solid-state battery).
[0046] 2. By doping with multiple elements and controlling the content of the doping elements, the entropy value of the doping layer is further increased, a high-entropy oxide interface layer is constructed, the interface stability between the positive electrode and the solid electrolyte is ensured, the cycle performance of the all-solid-state battery is significantly improved, and a new idea is provided for the interface modification of all-solid-state batteries.
[0047] 3. The doped layer is a perovskite-like phase, which has high ionic and electronic conductivity and low oxygen ion conductivity. It can act as an oxygen ion buffer layer, alleviate the escape of lattice oxygen on the positive electrode surface during charging and discharging, hinder the diffusion of decomposition byproducts of the solid electrolyte layer, and help enhance the interface stability between the positive electrode material and the solid electrolyte.
[0048] See also Figure 1As shown, the embodiment of the present application provides a method for preparing a multi-element interface-stable high-voltage all-solid-state battery positive electrode material, which specifically includes the following steps:
[0049] Step S1, dissolving a doping metal source in water or an organic reagent to obtain a precursor solution, wherein the doping metal source includes a doping element.
[0050] Specifically, a doping metal source is weighed and dissolved in deionized water or an organic reagent according to a certain molar ratio, and stirred to fully dissolve to obtain a precursor solution. The doping metal source contains doping elements, and the doping elements may include at least five of La, Ca, Mg, Lu, Eu, Al, Mo, Ta, Ti, V, Cr, Fe, Cu, Zn, Zr, and Nb. An appropriate amount of transition metal elements (such as L a , Lu, Mo and Eu) and non-transition metal elements (Ca, Al and Mg) can dope the layered oxide positive electrode material. Further, the doping elements can be composed of La, Ca, Mg, Lu and Eu.
[0051] In some embodiments, the doping metal source can be a chloride of the doping element. The chloride of the doping element has good solubility in water or organic solvents, can provide stable doping metal ions, and these metal ions can be evenly dispersed in the solution, which is beneficial to the uniformity and efficiency of subsequent reactions.
[0052] In some embodiments, the organic reagent may include one of anhydrous ethanol and N,N-dimethylacetamide (DMF). The above organic reagents all have good solubility and can effectively dissolve the above doping metal source to form a uniform solution. For example, DMF has good solubility and is particularly suitable for dissolving metal salts; it can also provide relatively mild reaction conditions, which is conducive to controlling factors such as temperature and solution pH during the doping process, and avoiding unnecessary structural damage to the material or side effects of chemical reactions.
[0053] Step S2, adding lithium-containing positive electrode particles to the precursor solution, mixing and filtering out the upper clear liquid to obtain solid particles, and obtaining a powder material after drying.
[0054] Specifically, a certain amount of lithium-containing positive electrode particles is added to the mixed solution obtained in step S1, the mixed solution is heated, fully mixed at a certain temperature, and a liquid-phase ion exchange reaction is performed. After the ion exchange reaction is completed, the obtained reaction product is subjected to solid-liquid separation, the upper clear liquid is filtered out, and the retained solid particles are washed with deionized water, and then dried in a blast oven at 80 to 100°C to obtain a powder material. The filtered upper clear liquid contains the above-mentioned mixed solution that has not reacted and the newly generated LiCl, and the obtained powder material is the doped positive electrode material. It can be understood that the method of heating the mixed solution includes but is not limited to an oil bath, a water bath or a metal bath, and the method that can achieve uniform heating of the solution is all possible.
[0055] In some embodiments, the lithium-containing positive electrode particles may be a lithium cobalt oxide positive electrode or a nickel-cobalt-manganese ternary positive electrode, etc.
[0056] Ion exchange reaction refers to the lithium ion (Li + ) and metal ions in the precursor solution (such as La 3+ , Ca 2+ Mg 2+ 、Lu 3+ 、Eu 3+ 、Al 3+ and Mo 6+ For example, lithium cobalt oxide is used as the lithium-containing positive electrode particle, and the reaction can be expressed as:
[0057] LiCoO2+MCl x →MCoO2+LiCl
[0058] Among them, M represents the metal ion in the solution, and x represents the coordination number in its corresponding compound.
[0059] In some embodiments, the mixing temperature can be 25°C to 100°C, and can further be 70°C to 90°C. Exemplarily, it can be 25°C, 35°C, 50°C, 70°C, 80°C, 90°C or 100°C, etc. Under the above temperature conditions, it is beneficial to increase the reaction rate and accelerate the diffusion of ions and the reaction.
[0060] In some embodiments, the mixing time can be 6 h to 24 h, and can further be 12 h to 24 h. Exemplarily, it can be 6 h, 9 h, 12 h, 15 h, 18 h, 21 h or 24 h, etc. Within the above time range, sufficient time can be guaranteed for the ion exchange reaction to ensure the effective replacement of lithium ions in the lithium-containing positive electrode particles with metal ions in the precursor solution.
[0061] In some embodiments, the molar amount of each component in the doping element is 5% to 20% of the molar amount of lithium in the lithium-containing positive electrode particles, for example, it can be 5% to 7% or 12% to 15%, and can be 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19% or 20%, etc. Controlling the molar amount of the doping element in the doping metal source in step S1 to be within the range of 5% to 20% of the molar amount of the lithium element can ensure that the doping element effectively replaces the lithium element in the lithium-containing positive electrode particles, reduces the volume expansion, irreversible phase change and side decomposition reaction of the battery during high-voltage cycling, thereby improving the safety of the battery and extending its service life; it can also effectively improve the electrochemical properties of the positive electrode material, such as improving energy density, discharge capacity and cycle stability.
[0062] Furthermore, the molar amount of each element in the doping element can be the same, and similar element contents can increase the irregularity of the structure and properties of the doping layer, thereby increasing the entropy value of the doping layer.
[0063] Step S3, sintering the powder material to obtain a high-voltage all-solid-state battery positive electrode material with a stable multi-element interface, wherein in the positive electrode material, the doping elements are located on the surface of the lithium-containing positive electrode particles to form a doping layer, and the doping layer is a multi-element high-entropy oxide interface layer of a perovskite-like phase.
[0064] Specifically, the dried powder material is placed in a heating device (such as a tubular atmosphere furnace), sintered under certain sintering conditions in an oxygen atmosphere, and then cooled to room temperature to obtain a surface high-entropy doped positive electrode material.
[0065] In some embodiments, the heating rate of sintering is 1°C / min to 5°C / min, and may further be 2°C / min to 4°C / min, and may be 1°C / min, 1.5°C / min, 2°C / min, 2.5°C / min, 3°C / min, 3.5°C / min, 4°C / min, 4.5°C / min, or 5°C / min, etc. During the sintering process, an appropriate heating rate can reduce the thermal stress of the material caused by the temperature gradient during the heating process, and help promote the uniformity of the reaction and the diffusion of the substance.
[0066] In some embodiments, the sintering temperature is 500°C to 700°C, and can further be 550°C to 650°C, and can be 500°C, 550°C, 600°C, 650°C or 700°C, illustratively. The above temperature range is conducive to the reaction and diffusion of the doping elements with the lithium-containing positive electrode particles, forming a uniform perovskite-like high-entropy doped metal oxide layer on the surface of the positive electrode material, and helping to ensure the structural stability of the positive electrode material and the phase change.
[0067] In some embodiments, the sintering time is 4 to 8 hours, and further can be 5 to 7 hours, and can be 4 hours, 5 hours, 6 hours, 7 hours or 8 hours, etc. Sufficient time can ensure that the doping elements are fully diffused and react with the lithium-containing positive electrode particles to construct a high entropy oxide interface layer.
[0068] In some embodiments, the sintering atmosphere is an oxygen atmosphere, which can provide a sufficiently oxidizing environment, help promote the oxidation reaction, maintain the stability and uniformity of oxygen in the material, and thereby ensure the formation of the doping layer and the stability of the material structure.
[0069] Compared with the prior art, the method for preparing a multi-element interface-stable high-voltage all-solid-state battery positive electrode material provided in the embodiment of the present application has the following beneficial effects:
[0070] 1. By using a variety of metal elements to perform high-entropy doping on layered oxide positive electrode materials, a positive electrode material with a high-entropy doped structure on the surface of a perovskite-like phase is obtained, which effectively alleviates the interfacial side reactions between the positive electrode material and the solid electrolyte, and at the same time inhibits the serious volume change and irreversible phase change of the positive electrode material during high-voltage cycling, reduces the risk of poor solid-solid contact on the positive electrode side, and improves the stability of the positive electrode interface of the all-solid-state battery prepared with the positive electrode material.
[0071] 2. The positive electrode material is prepared by liquid phase ion exchange method, and the molar ratio of each doping element to lithium element is adjusted to make it fully undergo replacement reaction. This method has high uniformity and ensures that the elements are uniformly doped into the positive electrode material by controlling the reaction conditions in the solution. It has strong controllability and can accurately control the reaction conditions, including solution concentration, temperature, etc. The reaction speed is fast, which is conducive to the efficient doping of doping elements.
[0072] 3. The preparation method has simple process, low cost, and easy control of the production process, and is suitable for large-scale industrial mass production of positive electrode materials.
[0073] The present application also provides an electrochemical device (such as a solid-state battery) including a positive electrode sheet, a negative electrode sheet, and a solid electrolyte, wherein the positive electrode sheet includes a positive electrode material, and the positive electrode material is a high-voltage all-solid-state battery positive electrode material with a multi-element interface stability as described above. Since the positive electrode material has the advantages of good chemical / electrochemical stability, good rate performance, and stable structure, the safety, cycle life, and rate performance of the lithium-ion battery at high voltage are improved.
[0074] The above-mentioned multi-element interface-stable high-voltage all-solid-state battery positive electrode material and its preparation method are further described below through specific examples.
[0075] Example 1
[0076] Step 1: Weigh a certain amount of metal chlorides (LaCl3, CaCl2, MgCl2, LuCl3 and EuCl3) in an equimolar ratio and add them to 5 mL of deionized water, stirring to fully dissolve them to obtain a precursor solution, in which the ion concentration of each element is 0.2 mol / L.
[0077] Step 2: Add 1 g of lithium cobalt oxide positive electrode material to the precursor solution obtained in step 1, heat it in an oil bath, perform ion exchange reaction at 90°C for 24 hours, separate the reaction product into solid and liquid, wash the solid particles with deionized water, and then dry them in a blast oven at 80°C to obtain a powder material.
[0078] Step 3: Place the powder material obtained in step 2 into a tubular atmosphere furnace, heat it to 600°C at a heating rate of 5°C / min in an oxygen atmosphere, and calcine it for 6 hours, then cool it to room temperature to obtain a surface high entropy doped lithium cobalt oxide positive electrode material (HE-LCO-90°C).
[0079] Example 2
[0080] Step 1: Weigh a certain amount of metal chlorides (LaCl3, CaCl2, MgCl2, LuCl3 and EuCl3) in an equimolar ratio and add them to 5 mL of deionized water, stirring to fully dissolve them to obtain a precursor solution, in which the ion concentration of each element is 0.2 mol / L.
[0081] Step 2: Add 1 g of lithium cobalt oxide positive electrode material to the precursor solution obtained in step 1, perform ion exchange reaction at 25°C for 24 hours, separate the reaction product into solid and liquid, wash the solid particles with deionized water, and then dry them in a blast oven at 80°C to obtain a powder material.
[0082] Step 3: Place the powder material obtained in step 2 into a tubular atmosphere furnace, heat it to 600°C at a heating rate of 5°C / min in an oxygen atmosphere, and calcine it for 6 hours, then cool it to room temperature to obtain a surface high entropy doped lithium cobalt oxide positive electrode material (HE-LCO-25°C).
[0083] Example 3
[0084] Step 1: Weigh a certain amount of metal chlorides (LaCl3, CaCl2, MgCl2, LuCl3 and EuCl3) in an equimolar ratio, add them to 5 mL of DMF solvent, stir to fully dissolve them, and obtain a precursor solution in which the ion concentration of each element is 0.2 mol / L.
[0085] Step 2: 1gLiNi 0.8 Co 0.1 Mn0.1 The O2 positive electrode material is added to the precursor solution obtained in step 1, and the ion exchange reaction is carried out at a temperature of 25°C for 24 hours. The reaction product is separated into solid and liquid, and the solid particles are washed with a DMF solvent, and then dried in a blast oven at 80°C to obtain a powder material.
[0086] Step 3: Place the powder material obtained in step 2 into a tubular atmosphere furnace, heat it to 600°C at a heating rate of 5°C / min in an oxygen atmosphere, and calcine it for 6 hours, then cool it to room temperature to obtain surface high entropy doped LiNi 0.8 Co 0.1 Mn 0.1 O2 positive electrode material (HE-NCM811).
[0087] Comparative Example 1
[0088] Step 1: Add 1 g of lithium cobalt oxide positive electrode material to deionized water, heat it in an oil bath, stir it at 90°C for 24 hours, separate the solid and liquid of the reaction product, wash the solid particles with deionized water, and then dry them in a blast oven at 80°C to obtain a powder material.
[0089] Step 2: Place the powder material obtained in step 1 into a tubular atmosphere furnace, heat it to 600°C at a heating rate of 5°C / min in an oxygen atmosphere, and calcine it for 6 hours, then cool it to room temperature to obtain an undoped lithium cobalt oxide positive electrode material (Bare-LCO).
[0090] Comparative Example 2
[0091] Step 1: 1g LiNi 0.8 Co 0.1 Mn 0.1 The O2 positive electrode material was added to the DMF solvent and stirred at 25°C for 24 hours. The reaction product was separated into solid and liquid. The solid particles were washed with DMF solvent and then dried in a blast oven at 80°C to obtain a powder material.
[0092] Step 2: The powder material obtained in step 1 is placed in a tubular atmosphere furnace, heated to 600°C at a heating rate of 5°C / min in an oxygen atmosphere, and calcined for 6 hours, and then cooled to room temperature to obtain undoped LiNi 0.8 Co 0.1 Mn 0.1 O2 positive electrode material (Bare-NCM811).
[0093] Comparative Example 3
[0094] Step 1: Weigh a certain amount of metal chlorides (LaCl3 and CaCl2) in an equimolar ratio and add them to 5 mL of deionized water, stirring to fully dissolve them to obtain a precursor solution, in which the ion concentration of each element is 0.2 mol / L.
[0095] Step 2: Add 1 g of lithium cobalt oxide positive electrode material to the precursor solution obtained in step 1, perform ion exchange reaction at 25°C for 24 hours, separate the reaction product into solid and liquid, wash the solid particles with deionized water, and then dry them in a blast oven at 80°C to obtain a powder material.
[0096] Step 3: Place the powder material obtained in step 2 into a tubular atmosphere furnace, heat it to 600°C at a heating rate of 5°C / min in an oxygen atmosphere, and calcine it for 6 hours, then cool it to room temperature to obtain La and Ca element-doped lithium cobalt oxide positive electrode material (LCO-LaCa).
[0097] Comparison test
[0098] The following tests were performed on the positive electrode materials obtained in Examples 1-3 and Comparative Examples 1-3, and corresponding test results were obtained.
[0099] 1. X-ray diffraction tests were performed on Example 1, Example 2 and Comparative Example 1. The results are as follows: Figure 2 The results were compared and analyzed, showing that the XRD patterns of Example 1, Example 2 and Comparative Example 1 were consistent, indicating that the addition of doped metal elements did not change the structure of the lithium cobalt oxide material.
[0100] 2. The positive electrode materials obtained in Examples 1-3 and Comparative Examples 1-3 were used to prepare all-solid-state batteries and perform electrochemical tests:
[0101] According to the mass ratio of positive electrode material: lithium indium chlorine solid electrolyte = 70:30, the mixed positive electrode powder was manually ground for 10 minutes and then installed into a solid-state mold battery. The specific process of solid-state battery installation is as follows: 80 mg of solid electrolyte powder was placed in a battery mold with a diameter of 10 mm and pressed under a pressure of 1 t. Then 10 mg of positive electrode composite powder was added to one side of the LIC particle and pressed at a pressure of 3.5 t. Finally, a piece of Li-In foil was placed on the other side of the LIC particle and pressed at a pressure of 0.5 t. In order to avoid In 3+ The possible effect of redox conversion between Li and In is to add Li between the Li-In anode and the solid electrolyte. 10 GeP2S 12 As a separator, the electrochemical performance of the assembled solid-state battery was tested at 25°C.
[0102] (1) The batteries prepared with the positive electrode materials in Examples 1-3 and Comparative Examples 1-2 were subjected to a long cycle test at a rate of 0.5C. The results are as follows: Figure 3A and Figure 3B shown.
[0103] Long cycle performance test method: At 25°C, the battery is charged and discharged at a current density of 0.5C in the charge and discharge range of 3.0-4.3V to obtain the specific capacity and coulomb efficiency of the battery. The lithium-ion battery is charged to 4.3V at a constant current of 0.5C (C represents the current rate, 1C = 160mA / g), and the charging capacity is recorded; then it is discharged at 0.5C to a cut-off voltage of 3.0V, and the discharge capacity is recorded, and the cycle is repeated 250 times. The 0.5C specific capacity of the positive electrode material is calculated by the discharge capacity, and the coulomb efficiency of the battery is calculated according to the following formula: Coulomb efficiency = (discharge capacity / charge capacity) * 100%.
[0104] The results show that in the voltage range of 3-4.3V, 25°C, and 0.5C rate, the batteries prepared from the positive electrode materials obtained in Examples 1 and 2 show better cycle stability than Comparative Example 1; and Example 3 also has better cycle stability than Comparative Example 2. This is because the high entropy doping layer formed in the positive electrode material of Examples 1-3 ensures the interface stability between the positive electrode and the solid electrolyte, significantly improving the cycle performance of the battery.
[0105] (2) The rate performance of the batteries prepared with the positive electrode materials in Examples 1-3 and Comparative Examples 1-3 was tested. The results are as follows: Figure 4A and Figure 4B shown.
[0106] Rate performance test method: At 25°C, the battery is charged and discharged at a current density of 0.1C / 0.2C / 0.5C / 1C / 0.1C in the charge and discharge range of 3-4.3V, and 5 cycles are performed under each current density condition to obtain the specific capacity and coulomb efficiency of the battery. The lithium-ion battery is charged to 4.3V at a constant current of 0.1C / 0.2C / 0.5C / 1C / 0.1C (C represents the current rate, 1C = 160mA / g), the charging capacity is recorded; then the battery is discharged at 0.1C / 0.2C / 0.5C / 1C / 0.1C to a cut-off voltage of 3.0V, the discharge capacity is recorded, the 0.1C specific capacity of the positive electrode material is calculated with the first discharge capacity, and the coulomb efficiency of the battery is calculated according to the following formula: coulomb efficiency = (first discharge capacity / first charge capacity) * 100%.
[0107] Compared with Comparative Examples 1 and 3, the batteries prepared from the positive electrode materials obtained in Examples 1 and 2 show better rate performance; compared with Comparative Example 2, Example 3 also has better rate performance. This is because Examples 1-3 doped the positive electrode materials with multiple elements with high entropy, which improved the rate performance of the battery.
[0108] (3) The battery prepared with the positive electrode materials in Example 1 and Comparative Example 1 was tested for cycle performance under high voltage. The results are as follows: Figure 5 shown.
[0109] Test method: Under normal temperature of 25℃, charge to 4.5V with a constant current of 0.5C (C represents current rate, 1C = 160mA / g), stop charging and record the charging capacity; then discharge to a cut-off voltage of 3.0V at 0.5C, record the discharge capacity, and calculate the coulombic efficiency of the battery according to the following formula: coulombic efficiency = (first discharge capacity / first charge capacity) * 100%.
[0110] The results show that compared with Comparative Example 1, the battery prepared with the positive electrode material obtained in Example 1 exhibits better high-voltage cycle performance because the perovskite-like high-entropy oxide interface layer of the positive electrode material alleviates the irreversible phase change and lattice oxygen loss of the positive electrode material during high-voltage cycling.
[0111] The above content is a further detailed description of the present invention in combination with specific / preferred embodiments, and it cannot be determined that the specific implementation of the present invention is limited to these descriptions. For ordinary technicians in the technical field to which the present invention belongs, without departing from the concept of the present invention, it can also make several substitutions or modifications to these described embodiments, and these substitutions or modifications should be regarded as belonging to the protection scope of the present invention. In the description of this specification, the description of the reference terms "an embodiment", "some embodiments", "preferred embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials or characteristics described in combination with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily target the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner. In the absence of mutual contradiction, those skilled in the art can combine and combine the different embodiments or examples described in this specification and the features of different embodiments or examples. Although the embodiments of the present invention and their advantages have been described in detail, it should be understood that various changes, substitutions and modifications can be made herein without departing from the scope of protection of the patent application.
Claims
1. A multi-element interface-stable high-voltage all-solid-state battery positive electrode material, characterized in that: It comprises a core and a doping layer located on the surface of the core, wherein the core is a lithium-containing layered oxide, and the doping layer is a multi-element high-entropy oxide interface layer of a perovskite-like phase.
2. The multi-element interface-stable high-voltage all-solid-state battery positive electrode material according to claim 1, characterized in that: The doping layer contains doping elements, and the doping elements include at least five of La, Ca, Mg, Lu, Eu, Al, Mo, Ta, Ti, V, Cr, Fe, Cu, Zn, Zr and Nb.
3. The multi-element interface-stable high-voltage all-solid-state battery positive electrode material according to claim 2, characterized in that: The doping elements are composed of La, Ca, Mg, Lu and Eu; the molar amount of each element in the doping elements is 5% to 20% of the molar amount of lithium in the lithium-containing positive electrode particles.
4. The multi-element interface-stable high-voltage all-solid-state battery positive electrode material according to any one of claims 1 to 3, characterized in that: The thickness of the doping layer is 20nm-30nm.
5. A method for preparing a multi-element interface-stable high-voltage all-solid-state battery positive electrode material, characterized in that: include: dissolving a plurality of doping metal sources in water or an organic reagent to obtain a precursor solution, wherein the doping metal sources include a doping element; Adding lithium-containing positive electrode particles to the precursor solution and mixing to generate solid particles, which are then dried to obtain a powder material; and The powder material is sintered to obtain the multi-element interface-stable high-voltage all-solid-state battery positive electrode material, wherein in the multi-element interface-stable high-voltage all-solid-state battery positive electrode material, the doping element is located on the surface of the lithium-containing positive electrode particles to form a doping layer, and the doping layer is a multi-element high-entropy oxide interface layer of a perovskite-like phase.
6. The method for preparing a multi-element interface-stable high-voltage all-solid-state battery positive electrode material according to claim 5, characterized in that: The doping elements include at least five of La, Ca, Mg, Lu, Eu, Al, Mo, Ta, Ti, V, Cr, Fe, Cu, Zn, Zr and Nb.
7. The method for preparing a multi-element interface-stable high-voltage all-solid-state battery positive electrode material according to claim 5, characterized in that: The doping elements consist of La, Ca, Mg, Lu and Eu; The molar amount of each element in the doping element is 5% to 20% of the molar amount of lithium in the lithium-containing positive electrode particles.
8. The method for preparing a multi-element interface-stable high-voltage all-solid-state battery positive electrode material according to any one of claims 5 to 7, characterized in that: In the step of adding the lithium-containing positive electrode particles into the precursor solution and mixing them, the mixing temperature is 25° C. to 100° C., and the mixing time is 6 h to 24 h.
9. The method for preparing a multi-element interface-stable high-voltage all-solid-state battery positive electrode material according to any one of claims 5 to 8, characterized in that: The heating rate of the sintering is 1°C / min to 5°C / min, the sintering temperature is 400°C to 800°C, the sintering time is 4h to 8h, and the sintering atmosphere is an oxygen atmosphere.
10. An electrochemical device, characterized in that: The electrochemical device comprises a positive electrode plate, a negative electrode and a sheet, and a solid electrolyte, wherein the positive electrode plate comprises a positive electrode material, and the positive electrode material is a multi-element interface-stabilized high-voltage all-solid-state battery positive electrode material as described in any one of claims 1 to 4 or a positive electrode material prepared by the preparation method of a multi-element interface-stabilized high-voltage all-solid-state battery positive electrode material as described in any one of claims 5 to 9.
Citation Information
Patent Citations
Method for preparing lithium battery positive electrode material with high-configuration entropy surface layer by solid-liquid phase method
CN116404153A
Nickel-based positive electrode material with entropy gradient and preparation method thereof
CN116632186A
High-entropy oxide doped and coated co-modified positive electrode material, preparation method and application
CN117223124A
High-capacity doped lithium manganate positive electrode material as well as preparation method and application thereof
CN118522881A
High-entropy oxide solid-state coated positive electrode material as well as preparation method and application thereof
CN118545773A
Cited By
Lithium-rich manganese-based positive electrode material surface coating layer and preparation method thereof
CN119742340A
